Pencatatan Akuntansi Retribusi Jasa Usaha Pada Disparbudpora Kabupaten Bengkalis - Een Erlina; Mira Misissaifi; Ema Nirwana; Zakaria Batubara; Nurmahadi Nurmahadi; Ade Suhartini; Yesifiayeni Yesifiayeni (CV. Civiliza Publishing, 2026)
This study aims to analyze the accounting treatment (recognition, measurement, and disclosure) of the levy for business services for recreational and sports venues at the Tourism, Culture, Youth and Sports Office (Disparbudpora) of Bengkalis Regency, as well as evaluate its conformity with Government Regulation (PP) No. 71 of 2010 concerning Accrual-Based Government Accounting Standards (SAP). This study uses a qualitative descriptive approach. Primary and secondary data were collected through semi-structured interviews with 10 key informants (regulators, business actors, and academics), field observations, and documentation of financial statements for the period 2021 to 2023. Data were analyzed using the Miles and Huberman model which included data reduction, data presentation, and conclusion drawn. The results of the study show that the technical recording and presentation of accounting for recreational levies at the Bengkalis Regency Disparbudpora has been structurally organized through the Regional Government Information System (SIPD) and complies with Government Regulation No. 71 of 2010. However, there are critical gaps at the revenue recognition stage. Due to the non-use of the Levy Determination Letter (SKR), the income of the Operational Report (LO) is practically only recognized when the cash is received by the treasurer, not when the right to collect arises, thus reflecting a cash-based transition. In addition, structural challenges in the form of mismatches in human resource competencies cause periodic delays in journal input and cash deposits from sub-district UPT units. Theoretically, this study enriches the public sector accounting literature regarding the limitation of the implementation of accruals on highly volatile non-official assessment income. Practically, this research is a strategic evaluation material for local governments to optimize institutional coordination, enforce strict daily deposit rules, and reorganize the competence of financial personnel in order to maintain agency accountability.